Canadian Association for Work & Labour Studies = L’Association canadienne d’études du travail et du syndicalisme (CAWLS, 2013)
The Canadian Association for Work and Labour Studies (CAWLS) is an academic association for scholars interested in work, workers, and labour. --Website

On the Move Partnership (2013)
Mobility for work is not new, but it is changing. Across the world a wide range of people are mobile for work – women and men, citizens and temporary foreign workers, new workers and those near retirement. From hours-long daily commutes, to travel that takes workers away from home for days, weeks, months and even years; from mobility within work (truck driving, shipping and others) to mobility to get to and from work; from cars and buses, to trains, ships and planes; from highly-paid top executive jobs, to minimum-wage service jobs; from natural resource dependent industry to natural wonder dependent tourism – the types of mobility are many and changing. The On the Move Partnership is a multi-year national scale research program with international links, investigating employment-related geographical mobility and its consequences for workers, families, employers, communities, and Canadian municipal, provincial and federal governments. --Website description